Diagnosis and treatment of adult asthma patients in Serbia: a 2022 experts group position statement. Issue 11 (2nd November 2022) - Vukoja, Marija; Kopitovic, Ivan; Lazic, Zorica; Milenkovic, Branislava; Stankovic, Ivana; Tomic-Spiric, Vesna; Zvezdin, Biljana; Hromis, Sanja; Cekerevac, Ivan; Ilic, Aleksandra; Vukcevic, Miodrag; Dimic-Janjic, Sanja; et al.
ABSTRACT: Introduction: Asthma is the most common non-communicable chronic lung condition across all ages. Epidemiological data indicate that many asthma patients in Serbia remain undiagnosed and untreated. The implementation of recent global advances in asthma management is limited due to the lack of a systematic approach, drug availability and regulatory affairs. In addition, the global coronavirus disease pandemic has posed a significant challenge, particularly in resource-limited settings. Areas covered: In this paper, we propose an algorithm for treating adult asthma patients in Serbia. We performed PubMed database search on published asthma clinical trials and guidelines from 1 January 2015 to 10 March 2020. The consensus process incorporated a modified Delphi method that included two rounds of e-mail questionnaires and three rounds of national asthma expert meetings. We focus on 1) objective diagnosis of asthma, 2) the implementation of up-to-date therapeutic options, and 3) the identification and referral of severe asthma patients to newly established severe asthma centers. Expert opinion: Regional specificities and variations in healthcare systems require the adaptation of evidence-based knowledge. Practical, clinically oriented algorithms designed to overcome local barriers in healthcare delivery may facilitate timely and adequate asthma diagnosis and the local implementation of current advances in asthma management.